NARRATIVE REVIEW: DRUG AVAILABILITY IN HEALTHCARE SERVICES IN INDONESIA - Sagitasari, Yanna; Widayanti, Anna Wahyuni; Yuniarti, Endang (Medical Sains : Jurnal Ilmiah Kefarmasian, 2024)
This narrative review delves into the availability of drugs within Indonesia’s healthcare services, analyzing 11 articles to uncover prevalent issues such as drug shortages, inadequate planning, and various factors influencing drug availability. This review underscores the critical need to ensure sufficient drug availability to enhance patient safety across healthcare settings. By examining journal articles, this review sheds light on the multifaceted aspects of drug availability, including planning management and the methods employed to evaluate their ability. The findings provide valuable insights into improving strategies for drug availability in hospitals and primary health care centers in Indonesia. This study found that out of the 11 articles reviewed, six reported insufficient drug availability, highlighting significant challenges in ensuring consistent access to necessary medications across different healthcare settings, including both primary healthcare centers and hospitals. Furthermore, the study identified geographical disparities in drug availability, with studies conducted outside Java Island reporting more severe drug shortages than those within Java Island. In summary, this study highlights the complex interplay between factors affecting drug availability in Indonesia, including geographical location, supply chain management, and procurement practices. This underscores the need for targeted interventions to address these challenges and improve drug availability across the healthcare system. Keywords: drug availability in Indonesia, patient safety, drug procurement in Indonesia, drug shortage.